2D Titanium Carbide (Ti3C2Tx) in Accommodating Intraocular Lens Design. (10th May 2020) - Ward, Emma J.; Lacey, Joseph; Crua, Cyril; Dymond, Marcus K.; Maleski, Kathleen; Hantanasirisakul, Kanit; Gogotsi, Yury; Sandeman, Susan
Abstract: While intraocular lenses (IOL) are used to restore visual acuity in cataract patients, they are limited in their development as no clinically available lens can effectively mimic the accommodative function of the eye's natural lens. The optoelectronic properties of 2D transition metal carbides and/or nitrides (MXenes), including high electronic conductivity, optical transparency, flexibility, biocompatibility, and hydrophilicity, suggest potential use within an accommodating IOL. This study investigates the use of Ti3 C2 T x (MXene) as a transparent, conductive electrode to allow changes in optical power. Ti3 C2 T x is synthesized and spin‐coated on hydrophobic acrylate IOLs, achieving a sheet resistance ranging from 0.2–1.0 kΩ sq −1 with 50–80% transmittance in the visible region. Human lens epithelial and monocytic cells show no cytotoxic nor inflammatory response to the coated lenses. An adjustable focus test cell is fabricated using a liquid crystal (LC) layer sandwiched between Ti3 C2 T x coatings on a solid support. Molecular reorientation of the LC layer, through an applied electric field, results in changes in optical power as objects viewed through the test cell appeared in and out of focus. This study is the first step toward the use of Ti3 C2 T x within an accommodative IOL design through demonstration of reversible, controlled, adjustable focus. Abstract : The development of intraocular lenses, used to treat cataracts, is limited as no clinically available lens has the ability to mimic the accommodative function of the eye's natural lens. Here, an optoelectronic approach to lens accommodation is investigated. The unique properties of the 2D transition metal carbides (MXenes) suggest their suitability for use within an accommodating lens design.